Adenovirus Type 21—Associated Acute Flaccid Paralysis during an Outbreak of Hand-Foot-and-Mouth Disease in Sarawak, Malaysia - Mong, How Ooi; Wong, See Chang; Daniela, Clear; David, Perera; Shekhar, Krishnan; Teresa, Preston; Tio, Phaik Hooi; Hugh, J. Willison; Brian, Tedman; Rachel, Kneen; Mary Jane, Cardosa; Tom, Solomon (Infectious Diseases Society of America, 2003)
We report the virological and clinical features of 8 children who presented with adenovirus-associated acute flaccid paralysis (AFP) during an epidemic of enterovirus type 71 (EV71)–associated hand-foot-and-mouth disease (HFMD) in Sarawak, Malaysia, in 1997. Neutralization tests and phylogenetic analysis revealed adenovirus type 21 (Ad21), although DNA restriction digests suggested that this virus was different from the prototype Ad21. Four children had upper-limb monoparesis, 2 had lower-limb monoparesis (one of whom had changes in the anterior spinal cord noted on magnetic resonance imaging), and 2 had flaccid paraparesis. At follow-up, 4 children were noted to have made full recoveries and 3 had residual flaccid weakness and wasting. Neurophysiological investigation revealed a mixture of axonal and demyelinating features in motor and sensory nerves, with denervation. These findings suggest that Ad21 might cause AFP by anterior horn cell damage or neuropathy of the brachial or lumbosacral plexus. The occurrence of these unusual adenovirus infections during an outbreak of EV71-associated HFMD suggests that an interaction between the 2 viruses may have occurred.